The ethics of care and the Newfoundland Paid Family Caregiver Program: An assessment - FitzGerald Murphy, Maggie (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2017)
The ethics of care has gained traction as a feminist normative lens from which to examine policies and policy issues (Hankivksy 2004; Mahon and Robinson 2011; Sevenhuijsen 2003; Sevenhuijsen et al. 2006). This paper aims to contribute to this growing literature by employing a critical ethics of care lens to assess a long-term care initiative in the province of Newfoundland and Labrador, Canada. This initiative, called the Newfoundland Paid Family Caregiver Program (NPFCP), allows eligible participants to pay family members for some care services. This analysis uncovers numerous tensions, both practical and theoretical, related to the way this program (re)shapes the caring relations of participants. Specifically, the paper discusses the ways in which this program downloads caring responsibilities onto the family, characterizes care as a private concern, and fails to facilitate competent and consistent care. Résumé L’éthique du care (voir aussi éthique de la sollicitude) a gagné en popularité en tant que notion féministe qui examine les politiques et les enjeux politiques (Hankivksy 2004; Mahon and Robinson 2011; Sevenhuijsen 2003; Sevenhuijsen et al. 2006). Cet article a pour but de contribuer à cette littérature grandissante en abordant l’éthique du care d’un oeil critique afin d’interpréter l’initiative de soin de longue durée dans la province de Terre-Neuve-et Labrador au Canada. Cette initiative, appelée Newfoundland Paid Family Caregiver Program (NPFCP) est un programme permettant aux participants admissibles d’obtenir des soins rémunérés d’un membre de sa famille. Cette analyse décèle de nombreuses tensions, pratiques et théoriques, liées à la manière dont le programme redéfinit la sollicitude des participants. Plus précisément, cet article aborde la façon dont ce programme transfert la responsabilité des soins à la famille, traite les soins comme une affaire privée et ne facilite pas les soins professionnels et continus. Mots clé: Éthique du care crucial ; soin de longue durée ; programmes de financement direct ; analyse normative des politiques